An Assessment of the Community Immersion of Ex Convicts in Barangay Nagka-Isang Nayon Novaliches, Quezon City: Vol.4, No.1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Based on the study conducted, it was discovered that individuals who are incarcerated andthen released back into society, commonly known as ex-offenders, face many obstaclesduring the process. The study aims to evaluate the level of community integration of ex-convicts in Brgy. Nagka-Isang Nayon, Novaliches Quezon City, mainly in terms of theirfinancial and work-related situations. Ex-convicts face many challenges, such as socialexclusion, maltreatment, aggression, stress, and anxiety, which affect their physical,psychological, and social well-being.The results of this research have the potential to form a solid foundation for future studies onex-offenders difficulties in reintegrating themselves into society. Additionally, it expedites theidentification of issues and potential fixes for better prison management. Every prisoner who isprepared and willing to change is also given the same treatment. Even yet, there are stillrestrictions depending on the seriousness of the crime and transgression committed by theprisoner.The recommended steps suggested in this study can also assist policymakers in the creationof specific programs and policies that aid ex-offenders in their efforts to re-enter thecommunity. Through this, the government can help offenders find their place in society andcontribute to its growth without causing trouble to anyone.
Keywords: Criminology